2016
DOI: 10.1371/journal.pone.0146764
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control Activities of Rice-Associated Bacillus sp. Strains against Sheath Blight and Bacterial Panicle Blight of Rice

Abstract: Potential biological control agents for two major rice diseases, sheath blight and bacterial panicle blight, were isolated from rice plants in this study. Rice-associated bacteria (RABs) isolated from rice plants grown in the field were tested for their antagonistic activities against the rice pathogens, Rhizoctonia solani and Burkholderia glumae, which cause sheath blight and bacterial panicle blight, respectively. Twenty-nine RABs were initially screened based on their antagonistic activities against both R.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 74 publications
0
51
1
1
Order By: Relevance
“…Sartori et al (2015) studied the biocontrol potential of phyllosphere microorganisms from maize against Exserohi lumturcicum, the causal agent of leaf blight. Shrestha et al (2016) investigated the prospects of biological control of rice-associated Bacillus against sheath blight and panicle blight of rice caused by Rhizoctonia solani and Burkholderia glumae, respectively. A variety of Bacillus isolates were observed to inhibit the sclerotial germination of the fungus, which could be attributed to the various antimicrobial secondary metabolites produced by the bacteria.…”
Section: Biocontrol Agentsmentioning
confidence: 99%
“…Sartori et al (2015) studied the biocontrol potential of phyllosphere microorganisms from maize against Exserohi lumturcicum, the causal agent of leaf blight. Shrestha et al (2016) investigated the prospects of biological control of rice-associated Bacillus against sheath blight and panicle blight of rice caused by Rhizoctonia solani and Burkholderia glumae, respectively. A variety of Bacillus isolates were observed to inhibit the sclerotial germination of the fungus, which could be attributed to the various antimicrobial secondary metabolites produced by the bacteria.…”
Section: Biocontrol Agentsmentioning
confidence: 99%
“…Si consideramos que la ausencia de bacteria patógena Burkholderia glumae, se debería a la menor producción de toxoflavin, que es dependiente del sistema de "quorum sensing" (Chen et al 2012, Goo et al 2010, Karki 2010y Devescovi et al 2007) y que algunas bacterias tendrían un potencial como agentes de control bio lógico (Shrestha et al 2016); diríamos que los resultados, sobre la no presencia de Burkholderia glumae, pero sí de otras espe cies de este mismo género, se explican con lo expresado anteriormente.…”
Section: Resultsunclassified
“…Miyagawa and Takaya [96] found that an avirulent strain of B. gladioli when applied onto rice panicles was very effective to reduce BPB severity. In the USA, five Bacillus amyloliquefaciens strains were found to be antagonistic against B. glumae in vitro and reduce BPB severity when applied at the heading stage in the field trials conducted in Louisiana [97]. When applied at the flowering stage, two strains of Bacillus sp., with antibacterial activities toward B. glumae, were demonstrated to reduce BPB severity by as much as 50% and increase grain yield by more than 11% in the field trials conducted in Texas [87,88].…”
Section: Biological Controlmentioning
confidence: 99%